THE IMPORTANCE OF VEGETATIVE REACTIVITY IN INTOXICATION OF THE BODY IN YOUNG CHILDREN WITH ACUTE PNEUMONIA - Fatima F. Xoltayeva (Scholar Express Journals, 2023)
One of the most significant problems of modern medicine is the steady increase in the prevalence of respiratory pathology. This pathology in childhood is represented mainly by inflammatory diseases. In turn, it remains important to study autonomic reactivity during intoxication of the body in young children with acute pneumonia.
Keywords: Autonomic reactivity; intoxication; pneumonia in children